Mindfulness-based interventions (MBI) for addiction control - review - Julia Szymonik; Justyna Woźniak; Sebastian Szopa; Karol Womperski; Jagoda Elias (Kazimierz Wielki University, 2024)
Abstract Introduction: Addiction is a complex phenomenon whose development may be related to many factors. Its treatment often includes behavioral therapy, social support, and in the case of substance addictions, may also include drug therapy. A key element of therapy is understanding the causes and mechanisms of addiction and developing the ability to cope with temptations and difficulties. In this particular context the utilization of mindfulness practices demonstrates promising potential in aiding the management of addiction. Purpose: Provide an overview of the current understanding regarding the efficacy of mindfulness training in addiction therapies. Description of the state of knowledge: The importance of employing mindfulness techniques in addressing addiction is steadily rising. Consistent practice of mindfulness offers advantages in addressing addictive behaviors by aiding individuals in comprehending and regulating impulses as well as managing intense cravings. Mindfulness facilitates an enhancement in self-awareness and recognition of personal reactions, proving especially beneficial in the process of recovery from addiction. Summary: Research shows that mindfulness training may be a promising intervention in addiction control because it increases self-control and promotes emotion regulation. However, further research is needed to evaluate the long-term effectiveness of mindfulness for addiction control. Keywords: mindfulness; addiction; addictive behavior; dependence; substance use disorder.